Pengaruh Kualitas Produk dan Citra Merek terhadap Kepuasan Konsumen Usaha Amplang MVM Kota Makassar - Marco Po; Tongam Sirait (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the effect of product quality and brand image on customer satisfaction at Amplang MVM, a traditional snack business in Makassar, Indonesia. Driven by increasing competition in the local snack industry, this research aims to provide insights into consumer behavior toward locally produced food products. Using a quantitative approach, data were collected from 100 respondents selected via Slovin’s formula, and analyzed using multiple linear regression. The findings reveal that both product quality and brand image have a significant and positive impact on customer satisfaction, with product quality contributing more dominantly. The coefficient of determination (R²) shows that these two variables explain 35.2% of the variation in satisfaction. The study emphasizes the importance of maintaining high product standards and strengthening brand perception to enhance consumer loyalty. These results offer practical implications for small businesses in the traditional food sector to develop sustainable strategies in a competitive market.